Safe flame-retardant gel electrolyte and lithium ion battery
By introducing phosphorus-containing and fluorine-containing flame retardant elements into the gel electrolyte, a three-dimensional network structure is formed, which solves the problem of electrochemical performance degradation caused by flame retardant additives in the prior art, and improves the safety and electrochemical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202510657348.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-26
AI Technical Summary
After the introduction of flame retardant additives in the existing gel electrolytes, the electrochemical performance of the electrochemical performance is reduced and the self-extinguishing time is limited, making it difficult to take into account both safety and battery performance.
Through in-situ polymerization, gel electrolytes are formed, and the phosphorus-containing and fluorine-containing flame retardant elements are introduced innovatively to form a three-dimensional network structure, combining lithium salts, organic solvents and functional additives to improve compatibility and safety performance.
Flame retardant and self-extinguishing are achieved, while avoiding excessive decrease in electrochemical performance, improving the safety performance and electrochemical performance of lithium-ion batteries.
Smart Images

Figure BDA0005412819030000031 
Figure BDA0005412819030000101 
Figure BDA0005412819030000111
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gel electrolytes, and in particular relates to a safe flame-retardant gel electrolyte and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have become the most important energy storage devices in the field of electrochemical energy storage. The development of their high energy density is accompanied by increasingly prominent safety issues. At present, commercial lithium-ion batteries mainly use liquid electrolytes, but their inherent flammability, volatility and leakage pose serious safety risks. Although solid electrolytes are highly anticipated due to their excellent mechanical strength, good thermal stability and wide electrochemical window, their low ionic conductivity limits their practical applications. In this context, gel electrolytes, as a polymer electrolyte with a three-dimensional network structure, combine the high ionic conductivity of liquid electrolytes and the high safety advantages of solid electrolytes, and have become a research hotspot in the current energy storage field.
[0003] The preparation process of gel electrolyte mainly includes non-in situ polymerization and in situ polymerization. The gel electrolyte formed based on in situ polymerization can fully penetrate into the electrode, achieving good gel electrolyte / electrode interface contact, which is conducive to large-scale practical applications. The gel electrolytes produced by in situ polymerization in the existing disclosed technologies are more focused on reducing the leakage and volatilization of the electrolyte, and the improvement of their safety is limited. Although some technologies introduce flame retardant additives, they will cause the loss of electrochemical performance and increase the interface impedance, and the improvement of the self-extinguishing time of the overall gel electrolyte is limited. Summary of the Invention
[0004] Based on the above technical problems, the present invention provides a safe flame-retardant gel electrolyte and a lithium-ion battery. To address the pain points of current liquid electrolytes, a gel electrolyte is formed by in-situ polymerization, and phosphorus-containing flame retardant elements and fluorine-containing flame retardant elements are innovatively introduced to achieve dual-element synergistic flame retardancy and electrochemical performance. This overcomes the shortcomings of existing gel electrolytes that result in decreased electrochemical performance due to the introduction of flame retardant additives, improves the compatibility of the gel electrolyte with electrodes, enhances the safety performance of the battery and reduces costs.
[0005] The present invention provides a safe flame-retardant gel electrolyte, which is obtained by heating and cross-linking a gel electrolyte;
[0006] The gel electrolyte comprises a basic electrolyte, a gel polymerization monomer, a cross-linking agent and an initiator; the basic electrolyte comprises a lithium salt, an organic solvent and an additive; and the gel polymerization monomer comprises a phosphorus-containing flame retardant monomer and a fluorine-containing flame retardant monomer.
[0007] In the present invention, the gel electrolyte is essentially prepared by in-situ thermal polymerization of lithium salt, organic solvent, additive, phosphorus-containing flame retardant monomer, fluorine-containing flame retardant monomer and cross-linking agent under initiator conditions. The formed gel electrolyte mainly consists of a polymer with a three-dimensional network structure and electrolyte lithium salt, organic solvent and functional additives uniformly dispersed and swollen in the three-dimensional network polymer structure. Compared with traditional flame-retardant gel electrolytes, it not only has flame retardancy, but also has self-extinguishing properties, while avoiding excessive degradation of electrochemical performance. When used in lithium-ion batteries, it ensures the safety and electrochemical performance of lithium-ion batteries.
[0008] Preferably, the lithium salt is at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(oxalatoborate) (LiBOB) or lithium difluorooxalatoborate (LiDFOB);
[0009] Preferably, the concentration of the lithium salt in the basic electrolyte is 0.5-2 mol / L.
[0010] Preferably, the organic solvent is at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or 1,2-dimethoxyethane (DME).
[0011] Preferably, the additive is at least one of fluoroethylene carbonate (FEC), methyl trifluoroethyl carbonate (FEMC), bisfluoroethylene carbonate (DFEC), vinyl sulfate (DTD), vinylene carbonate (VC), propenyl-1,3-sultone (PST), methylene methanedisulfonate (MMDS), tris(trimethylsilyl)phosphine (TMSP), methyl difluoroacetate (MFA), ethyl difluoroacetate (EFA), bis(2,2,2-trifluoroethyl) carbonate (TFEC), lithium difluorophosphate (LiPO2F2), perfluorobutyl methyl ether, phenyl dichlorophosphate or fluorobenzene (FB);
[0012] Preferably, based on the total mass of the basic electrolyte, the additive accounts for 0.1-20 wt%.
[0013] Preferably, the phosphorus-containing flame retardant monomer is at least one of diethyl vinyl phosphonate (DEVP), diethyl allyl phosphate (DAP), triallyl phosphate (TAP) or 2-oxyphosphinyl tris(oxy-2,1-ethylene) acrylate (TAEP), and the fluorine-containing flame retardant monomer is at least one of hexafluorobutyl acrylate (HFBA), dodecafluoroheptyl methacrylate (DFHMA) or trifluoroethyl methacrylate (TFMA);
[0014] Preferably, the molar ratio of the phosphorus-containing flame retardant monomer to the fluorine-containing flame retardant monomer is 1:0.5-1.5; preferably, based on the total mass of the basic electrolyte, the proportion of the gel polymerized monomer is 5-35 wt%.
[0015] Preferably, the crosslinking agent is at least one of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate (ETEA), ethoxylated trimethylolpropane triacrylate (ETPTA), triethylene glycol dimethacrylate (TEGDMA) or trimethylol propane ethoxylate triacrylate;
[0016] Preferably, the molar ratio of the cross-linking agent to the phosphorus-containing flame retardant monomer is 0.5-1.5:1;
[0017] Preferably, the gel polymerization monomer further includes at least one of methyl methacrylate (MMA), ethyl methacrylate (EMA) or polyethylene glycol diacrylate (PEGDA).
[0018] Preferably, the gel polymerization monomer further comprises a crown ether-containing alkenyl silicon monomer, the structural formula of which is shown below:
[0019]
[0020] Preferably, the crown ether-containing alkenyl silicon monomer is prepared by the following method: performing a substitution reaction on dimethylvinylchlorosilane and 4'-aminobenzo-18-crown-6;
[0021] Preferably, the mass ratio of the crown ether-containing alkenyl silicon monomer to the phosphorus-containing flame retardant monomer is 0.1-1:1.
[0022] In the present invention, a crown ether-containing alkenyl silicon monomer is involved in cross-linking polymerization. On the one hand, crown ether groups can be introduced into the polymer segments of the gel electrolyte. Crown ethers have a special cyclic structure, the size of the cavities inside them matches the size of lithium ions, and can selectively complex with lithium ions, thereby improving the electrolyte conductivity and the electrochemical performance when used in batteries. On the other hand, silicon-containing groups can also be introduced into the polymer segments of the gel electrolyte. Silicon-containing groups can synergistically act with phosphorus to significantly increase the flame retardant properties of the gel electrolyte, further improving its safety performance.
[0023] Preferably, the initiator is at least one of azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO), di(4-tert-butylcyclohexyl) peroxydicarbonate, dodecanoyl peroxide or diisopropyl peroxydicarbonate;
[0024] Preferably, based on the total mass of the basic electrolyte, the initiator accounts for 0.01-0.5 wt%.
[0025] Preferably, the basic electrolyte, gel polymerization monomer, cross-linking agent and initiator are mixed, injected into the battery cell, and heated for cross-linking polymerization to form the gel electrolyte;
[0026] Preferably, the heating cross-linking polymerization temperature is 50-80° C. and the time is 8-24 hours.
[0027] The present invention also provides a lithium ion battery comprising the above-mentioned gel electrolyte.
[0028] In the present invention, the lithium-ion battery further comprises: a positive electrode plate, namely, a positive electrode active material; a negative electrode plate, namely, a negative electrode active material; and a gel electrolyte located between the positive electrode plate and the negative electrode plate.
[0029] The preparation method of the positive electrode sheet and the negative electrode sheet is as follows:
[0030] A precise metering system is used to prepare a homogeneous positive electrode slurry with positive electrode active material, binder and conductive agent in a predetermined mass ratio. The slurry is evenly coated on the surface of the aluminum foil current collector by high-precision coating equipment, and the coating surface density is controlled within a certain range. The slurry is then densified by a double-roll calender with the pressure maintained at 80-100 MPa, and finally cut into positive electrode sheets of designed specifications.
[0031] The preparation of negative electrode sheets adopts a similar process, in which the negative electrode active material, binder and conductive agent are prepared into negative electrode slurry in a predetermined proportion; the slurry is evenly coated on the copper foil current collector using micro-gravure coating technology, and the coating surface density is controlled within a certain range; after the roller pressing process, the porosity of the sheet is controlled within the range of 30-35%, and finally it is cut into negative electrode sheets of corresponding sizes; the entire preparation process is carried out in a dry environment with a humidity of ≤1% to ensure the stability of the electrode performance.
[0032] The preparation method of the gel electrolyte is specifically as follows:
[0033] Lithium salt and additives are dissolved in an organic solvent to obtain a basic electrolyte, gel polymerization monomers are added, mixed evenly, and then an initiator is added. After sufficient dissolution, a gel electrolyte is obtained, and then in-situ polymerization is initiated by thermal polymerization to obtain the gel electrolyte.
[0034] The preparation method of the lithium ion battery is as follows:
[0035] The battery cells are sealed using a vacuum packaging system, with the vacuum maintained at 10-3Pa. The packaged battery cells are left at 25±2°C for 12-24 hours to allow the electrolyte to fully infiltrate the electrode materials. The battery cells are then placed in a programmed temperature-controlled reactor, heated to a certain temperature, and maintained for 8-24 hours to complete the in-situ thermal polymerization reaction, ultimately obtaining a flame-retardant gel polymer electrolyte lithium-ion battery with a three-dimensional cross-linked network structure.
[0036] In the present invention, the process of injecting liquid first and then polymerizing ensures good compatibility between the electrolyte and the electrode interface, while improving the safety performance of the battery.
[0037] In the above preparation method, the positive electrode active material is preferably lithium hexafluorophosphate (LFP) or at least one of layered metal oxides, such as nickel cobalt manganese ternary material (NCM811 or NCM622 or NCM523), lithium cobalt oxide (LCO), and the mixing mass ratio of the positive electrode active material, binder, and conductive agent is (92-97): (1-3): (2-5).
[0038] In the above-mentioned preparation method, the negative electrode active material is preferably at least one of an artificial graphite negative electrode, a natural graphite negative electrode, or a silicon-carbon negative electrode, and the mixing mass ratio of the negative electrode active material, the binder, and the conductive agent is (92-97):(1-3):(2-5).
[0039] Compared with the prior art, the present invention has the following technical effects:
[0040] The gel electrolyte described in this invention incorporates phosphorus-containing flame retardant elements and fluorine into the polymer backbone or side chains, and encapsulates the electrolyte within a three-dimensional polymer network. This not only prevents electrolyte leakage and increases thermal stability, essentially raising the upper threshold for thermal runaway, but also improves the battery's overall plasticity or strength. The introduction of fluorine-containing monomers minimizes electrochemical performance losses and significantly reduces the risks associated with external forces such as collisions. Overall, the resulting lithium-ion battery's overall safety is enhanced while minimizing performance losses, achieving a balanced balance between safety and electrochemical performance. DETAILED DESCRIPTION
[0041] Hereinafter, the present invention will describe the technical solution in detail through specific embodiments. However, it should be clearly stated that these embodiments are provided for illustration only and are not to be construed as limiting the scope of the present invention.
[0042] Example 1
[0043] A lithium-ion battery is prepared by the following preparation method:
[0044] (1) In an argon-filled glove box, EC, EMC, DEC and PC were mixed in a volume ratio of 1:1:1:1, LiPF6 was added, and the mixture was stirred until completely dissolved to obtain a 1 mol / L LiPF6 electrolyte. FEC and FEMC were then added, and the mass percentage of FEC was 5% and the mass percentage of FEMC was 5% based on the total mass of the basic electrolyte as 100%. After thorough stirring and mixing for 2 hours, a basic electrolyte was obtained. DEVP, HFBA and ETEA were added to the basic electrolyte as gel polymerization monomers, and the molar ratio of DEVP, HFBA and ETEA was 1:1:1. Based on the total mass of the basic electrolyte as 100%, the total mass percentage of DEVP, HFBA and ETEA was 25%. AIBN was also added, and the mass percentage of AIBN was 0.04% based on the total mass of the basic electrolyte as 100%. After stirring until completely dissolved, a gel electrolyte was obtained.
[0045] (2) NCM622, PVDF and conductive carbon black were prepared into a positive electrode slurry in a mass ratio of 95:2:3, and the obtained positive electrode slurry was coated on the positive electrode current collector aluminum foil by a coating machine, and the positive electrode sheet was prepared by rolling, slitting and welding processes; artificial graphite, styrene-butadiene rubber and conductive carbon black were prepared into a negative electrode slurry in a mass ratio of 95:2:3, and the obtained negative electrode slurry was coated on the negative electrode current collector copper foil by a coating machine, and the negative electrode sheet was prepared by rolling, slitting and welding processes; the obtained positive electrode sheet and negative electrode sheet were baked in an oven until the moisture content was less than 200 ppm;
[0046] (3) The positive electrode sheet, the negative electrode sheet and the separator are wound into a battery cell, which is then placed in a lithium-ion battery packaging bag and sealed on the top and sides with an aluminum-plastic film. The gel electrolyte is injected into the battery cell, which is sealed and allowed to stand for 72 hours. The cell is then placed at 60° C. and in situ polymerized for 24 hours to form a gel electrolyte, thereby obtaining the lithium-ion battery.
[0047] Example 2
[0048] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), DAP, DFHMA, MMA and ETPTA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of DAP, DFHMA, MMA and ETPTA is 1:1:0.5:0.5.
[0049] Example 3
[0050] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), TAP, TFMA and PEGDA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of TAP, TFMA and PEGDA is 1:1:1.
[0051] Example 4
[0052] A lithium ion battery is prepared according to the preparation method described in Example 1, except that in step (1), the molar ratio of DEVP, HFBA and ETEA is 1:0.5:1.5.
[0053] Example 5
[0054] A lithium ion battery is prepared according to the preparation method described in Example 1, except that in step (1), the molar ratio of DEVP, HFBA and ETEA is 1:1.5:0.5.
[0055] Example 6
[0056] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), DEVP, HFBA, a crown ether-containing alkenyl silicon monomer, and ETEA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of DEVP, HFBA, the crown ether-containing alkenyl silicon monomer, and ETEA is 1:1:0.5:1.
[0057] The crown ether-containing alkenyl silicon monomer is prepared by the following method: 4'-aminobenzo-18-crown-6, dimethylvinylchlorosilane, N-methylpyrrolidone and triethylamine are uniformly mixed in a molar ratio and volume ratio of 50mmol:55mmol:100mL:20mL, the temperature is raised to 70°C, the mixture is stirred and reacted for 4 hours, low-boiling substances are removed by vacuum rotary evaporation, and deionized water is added for extraction and washing twice to obtain the crown ether-containing alkenyl silicon monomer.
[0058] Example 7
[0059] A lithium ion battery is prepared according to the preparation method described in Example 1, except that in step (1), FEC is added instead of FEC and FEMC, and the mass percentage of FEC is 10% based on the total mass of the basic electrolyte being 100%.
[0060] Comparative Example 1
[0061] A lithium-ion battery is prepared by the following preparation method:
[0062] (1) In an argon-filled glove box, EC, EMC, DEC, and PC were mixed in a volume ratio of 1:1:1:1, and LiPF6 was added. After stirring until completely dissolved, a 1 mol / L LiPF6 electrolyte was obtained. FEC and FEMC were then added. Based on the total mass of the basic electrolyte being 100%, the mass percentage of FEC was 5%, and the mass percentage of FEMC was 5%. After thorough stirring for 2 h, the basic electrolyte was obtained.
[0063] (2) NCM622, PVDF and conductive carbon black were prepared into a positive electrode slurry in a mass ratio of 95:2:3, and the obtained positive electrode slurry was coated on the positive electrode current collector aluminum foil by a coating machine, and the positive electrode sheet was prepared by rolling, slitting and welding processes; artificial graphite, styrene-butadiene rubber and conductive carbon black were prepared into a negative electrode slurry in a mass ratio of 95:2:3, and the obtained negative electrode slurry was coated on the negative electrode current collector copper foil by a coating machine, and the negative electrode sheet was prepared by rolling, slitting and welding processes; the obtained positive electrode sheet and negative electrode sheet were baked in an oven until the moisture content was less than 200 ppm;
[0064] (3) The positive electrode sheet, the negative electrode sheet and the separator are wound into a battery cell, which is then placed in a lithium-ion battery packaging bag and sealed on the top and sides with aluminum-plastic film. The basic electrolyte is injected into the battery cell, sealed, and allowed to stand for 72 hours to obtain the lithium-ion battery.
[0065] Comparative Example 2
[0066] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), MMA and ETEA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of MMA to ETEA is 1:1.
[0067] Comparative Example 3
[0068] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), DEVP and ETEA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of DEVP to ETEA is 1:1.
[0069] Comparative Example 4
[0070] A lithium-ion battery is prepared according to the preparation method described in Example 1, except that in step (1), HFBA and ETEA are added to the basic electrolyte as gel polymerization monomers, and the molar ratio of HFBA to ETEA is 1:1.
[0071] The gel electrolytes or electrolytes formed in the examples and comparative examples were ignited by a fire source. After the fire source was removed, the flame retardant properties were observed and the self-extinguishing time was calculated.
[0072] The lithium-ion batteries described in the examples and comparative examples were placed in an environment at 25°C, discharged at 0.2C to the lower voltage limit, and allowed to stand for 10 minutes. The batteries were then charged at a constant current of 0.5C to the upper voltage limit (4.3V), and then charged at a constant voltage of 4.3V to a current of 0.05C, and allowed to stand for 5 minutes. A high-temperature resistant steel needle with a diameter of 2.0±0.2 mm was used to penetrate the battery plates at right angles to the plate at a speed of 25 mm±2.5 mm / s, preferably near the geometric center of the punctured surface (with the needle remaining in the battery). The batteries were observed for 30 minutes to see if they caught fire or exploded.
[0073] The lithium-ion batteries described in the examples and comparative examples were placed at 25°C, discharged at a constant current of 0.5C to the lower limit voltage of the battery, and allowed to stand for 5 minutes; then charged at a constant current of 0.5C to the upper limit voltage, and then charged at a constant voltage of the upper limit voltage to a current of 0.05C, and allowed to stand for 5 minutes; then discharged at a constant current of 0.5C to the lower limit voltage, and the discharge capacity was recorded as the first discharge capacity.
[0074] The lithium-ion batteries described in the examples and comparative examples were placed at 25°C, discharged at a constant current of 0.5C to a lower voltage limit (2.8V), and allowed to stand for 5 minutes; then charged at a constant current of 0.5C to an upper voltage limit (4.3V), then charged at a constant voltage of 4.3V to a current of 0.05C, and allowed to stand for 5 minutes; then discharged at a constant current of 0.5C to a voltage of 2.8V, and allowed to stand for 5 minutes. This constituted one charge and discharge cycle. The charge / discharge cycle was repeated until the ratio of the discharge capacity to the initial discharge capacity in a certain cycle was ≤80%. The number of cycles experienced was the cycle life.
[0075] Table 1 Comparison of the performance of the corresponding gel electrolytes of the examples and comparative examples
[0076]
[0077]
[0078] As can be seen from Table 1 above, the overall safety performance of the lithium-ion battery described in the embodiment is enhanced, while the loss of battery performance is minimized, taking both safety and electrochemical performance into account.
[0079] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A safe flame-retardant gel electrolyte, characterized in that: It is obtained by heating and cross-linking the gel electrolyte; The gel electrolyte comprises a basic electrolyte, a gel polymerization monomer, a cross-linking agent and an initiator; the basic electrolyte comprises a lithium salt, an organic solvent and an additive; and the gel polymerization monomer comprises a phosphorus-containing flame retardant monomer and a fluorine-containing flame retardant monomer.
2. The safe flame-retardant gel electrolyte according to claim 1, characterized in that: The lithium salt is at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bis(oxalatoborate) or lithium difluorooxalatoborate; Preferably, the concentration of the lithium salt in the basic electrolyte is 0.5-2 mol / L.
3. The safe flame-retardant gel electrolyte according to claim 1 or 2, characterized in that: The organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate or 1,2-dimethoxyethane.
4. The safe flame-retardant gel electrolyte according to any one of claims 1 to 3, characterized in that: The additive is at least one of fluoroethylene carbonate, methyl trifluoroethyl carbonate, bisfluoroethylene carbonate, vinyl sulfate, vinylene carbonate, propenyl-1,3-sultone, methylene methanedisulfonate, tris(trimethylsilyl)phosphine, methyl difluoroacetate, ethyl difluoroacetate, bis(2,2,2-trifluoroethyl) carbonate, lithium difluorophosphate, perfluorobutyl methyl ether, phenyl dichlorophosphate or fluorobenzene; Preferably, based on the total mass of the basic electrolyte, the additive accounts for 0.1-20 wt%.
5. The safe flame-retardant gel electrolyte according to any one of claims 1 to 4, characterized in that: The phosphorus-containing flame retardant monomer is at least one of diethyl vinylphosphonate, diethyl allyl phosphate, triallyl phosphate or 2-oxyphosphinyl tris(oxy-2,1-ethylene) acrylate, and the fluorine-containing flame retardant monomer is at least one of hexafluorobutyl acrylate, dodecafluoroheptyl methacrylate or trifluoroethyl methacrylate; Preferably, the molar ratio of the phosphorus-containing flame retardant monomer to the fluorine-containing flame retardant monomer is 1:0.5-1.5; preferably, based on the total mass of the basic electrolyte, the proportion of the gel polymerized monomer is 5-35 wt%.
6. The safe flame-retardant gel electrolyte according to any one of claims 1 to 5, characterized in that: The crosslinking agent is at least one of 1,6-hexanediol diacrylate, pentaerythritol tetraacrylate, ethoxylated trimethylolpropane triacrylate, triethylene glycol dimethacrylate or trimethylol propane ethoxylate triacrylate; Preferably, the molar ratio of the cross-linking agent to the phosphorus-containing flame retardant monomer is 0.5-1.5:1; Preferably, the gel polymerization monomer further includes at least one of methyl methacrylate, ethyl methacrylate or polyethylene glycol diacrylate.
7. The safe flame-retardant gel electrolyte according to any one of claims 1 to 6, characterized in that: The gel polymerization monomer also includes a crown ether alkenyl silicon monomer, the structural formula of which is shown below: Preferably, the crown ether-containing alkenyl silicon monomer is prepared by the following method: performing a substitution reaction on dimethylvinylchlorosilane and 4'-aminobenzo-18-crown-6; Preferably, the molar ratio of the crown ether-containing alkenyl silicon monomer to the phosphorus-containing flame retardant monomer is 0.1-1:
1.
8. The safe flame-retardant gel electrolyte according to any one of claims 1 to 7, characterized in that: The initiator is at least one of azobisisobutyronitrile, dibenzoyl peroxide, di(4-tert-butylcyclohexyl)peroxydicarbonate, dodecanoyl peroxide or diisopropyl peroxydicarbonate; Preferably, based on the total mass of the basic electrolyte, the initiator accounts for 0.01-0.5 wt%.
9. The safe flame-retardant gel electrolyte according to any one of claims 1 to 8, characterized in that: The gel electrolyte is formed by mixing a basic electrolyte, a gel polymerization monomer, a cross-linking agent and an initiator, injecting the mixture into a battery cell, and heating and cross-linking polymerization. Preferably, the heating cross-linking polymerization temperature is 50-80° C. and the time is 8-24 hours.
10. A lithium ion battery, characterized in that: The invention comprises the gel electrolyte according to any one of claims 1 to 9.
Citation Information
Cited By
Semi-solid battery and preparation method thereof
CN121507079A
Flame-retardant gel electrolyte, preparation method thereof and lithium ion battery containing electrolyte
CN121507084A